2011
DOI: 10.1093/molbev/msr002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Selection at Melanin Synthesis Pathway Loci during Silkworm Domestication

Abstract: The domesticated silkworm (Bombyx mori) was domesticated from wild silkworm (Bombyx mandarina) more than 5,000 years ago. During domestication, body color between B. mandarina and B. mori changed dramatically. However, the molecular mechanism of the silkworm body color transition is not known. In the present study, we examined within-and between-species nucleotide diversity for eight silkworm melanin synthesis pathway genes, which play a key role in cuticular pigmentation of insects. Our results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 84 publications
4
58
0
1
Order By: Relevance
“…Guo et al (2011) demonstrated that a marked decrease in π value of B. mori Def A gene relative to that of Chinese B. mandarina supported that the Def A gene was under artificial selection during domestication. A similar result was presented by Yu et al (2011). The present result is consistent with those of Guo et al (2011) and Yu et al (2011), suggesting that CAD is a candidate gene for silkworm domestication.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Guo et al (2011) demonstrated that a marked decrease in π value of B. mori Def A gene relative to that of Chinese B. mandarina supported that the Def A gene was under artificial selection during domestication. A similar result was presented by Yu et al (2011). The present result is consistent with those of Guo et al (2011) and Yu et al (2011), suggesting that CAD is a candidate gene for silkworm domestication.…”
Section: Discussionsupporting
confidence: 92%
“…A similar result was presented by Yu et al (2011). The present result is consistent with those of Guo et al (2011) and Yu et al (2011), suggesting that CAD is a candidate gene for silkworm domestication. As described above, the BGIBMGA006816-TA in the Silkworm Genome Database including the CAD gene was not found in the list of genes that represent good candi-dates for domestication genes (Xia et al, 2009) and therefore was considered to be a neutral gene for artificial selection (Xia et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When comparing the result with those of nuclear genes, we can use limited amount of information on genetic variation in nuclear genes. For example, Kim et Yu et al (2011) demonstrated that Tyrosine hydroxylase (TH) gene had extremely low amount of nucleotide diversity relative to Chinese B. mandarina. The TH gene was considered to be one of the target genes for silkworm domestication through multiple approaches of population genetic analyses.…”
Section: Segregation Sites In the Coi Coding Regionmentioning
confidence: 99%